Dealloyed sodium ion battery negative electrode material and preparation method thereof

By using pre-plating and electroplating technology to form a nano-scale metal mesh or three-dimensional porous carbon skeleton structure in the negative electrode materials of sodium ion battery, the problem of slow kinetics and volume expansion of sodium ion battery is solved, and the circulation performance and specific capacity of the material are improved. Achieve better battery performance.

CN114725387BActive Publication Date: 2025-01-10GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210155245.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-21
Publication Date
2025-01-10
Estimated Expiration
2042-02-21

AI Technical Summary

Technical Problem

Due to the slow sodium ion kinetics and insufficient material circulation performance, sodium ion batteries have limited application in energy storage systems, especially the problem of volume expansion of alloy negative electrode materials during charging and discharging, resulting in performance attenuation.

Method used

Using dealloyed sodium ion battery negative electrode material composed of solid carbon particles or nano-scale metal mesh, nano-scale metal mesh or three-dimensional porous carbon framework structure is formed through pre-plating and electroplating technology to enhance the cyclic performance and mechanical strength of the material and slow down the Effects of volume change.

Benefits of technology

The cycling performance and specific capacity of the negative electrode material of sodium ion battery is improved, the contact area between the electrode and the electrolyte is increased, the volume changes during buffering and discharge are improved, and the high capacity and rate performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114725387B_ABST
    Figure CN114725387B_ABST
Patent Text Reader

Abstract

The present invention discloses a dealloyed sodium ion battery negative electrode material and a preparation method thereof. The sodium ion battery negative electrode material is composed of solid carbon particles and a nano-scale metal mesh coated on the surface of the solid carbon particles, or is composed of a nano-scale metal mesh and a carbon skeleton supported by the nano-scale metal mesh, wherein the carbon skeleton is hollow or three-dimensionally porous, and the nano-scale metal mesh is composed of at least one of Sn, Pb, Bi, Ge or Sb. The combination of the metal mesh and the carbon material can improve the strength and conductivity of the particles, and the three-dimensional porous or hollow carbon skeleton structure can further improve the specific surface area of ​​the material, which is more conducive to the deintercalation of sodium ions, and can improve the cycle performance and specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a dealloyed sodium ion battery negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries play an important role in energy storage modules for electric vehicles and handheld electronic devices. However, the application of lithium-ion batteries in the future field of renewable energy generation and energy storage is limited by limited lithium resources and high energy storage costs. Sodium-ion batteries have a similar electrochemical reaction principle to lithium-ion batteries, and sodium resources are abundant, widely distributed, and low-cost. In the case that the large-scale development of lithium-ion batteries may be constrained by the bottleneck of lithium resource shortage, sodium-ion batteries are expected to be used in large-scale energy storage systems, and therefore have received widespread attention from the scientific research and industrial communities. However, due to the large radius and heavy mass of sodium ions, the kinetics of sodium ions in electrode materials are slow, which hinders the practical application of sodium-ion batteries. Therefore, it is more difficult to find suitable sodium ion host negative electrode materials than lithium-ion battery negative electrode materials.

[0003] Graphite is the most mature negative electrode material for lithium-ion batteries. It has been confirmed that when graphite is used as the negative electrode of sodium-ion batteries, in carbonate electrolytes, sodium ions can only be embedded in graphite to form 8-order NaC 64 Compounds. In the past decade, the negative electrode materials of sodium-ion batteries have developed rapidly, and researchers have developed a series of hard carbons, heteroatom-doped carbon materials, intercalation compounds, conversion and alloying negative electrodes.

[0004] At present, high-capacity negative electrode materials are mainly concentrated in metal oxide / sulfide materials, alloy materials, etc. Among them, negative electrode materials with alloy mechanism have attracted much attention from researchers due to their higher specific capacity and better safety, such as tin-antimony alloy, tin-phosphorus compound and SnGeSb ternary alloy. SnSb alloy has a theoretical specific capacity of up to 853mAh / g, which is a very potential negative electrode material for sodium ion batteries. However, its volume expansion during the charging and discharging process causes the material to pulverize and then leads to rapid attenuation of battery performance. For example, the volume expansion rate of tin-based materials during the alloying-dealloying process reaches 358%.

[0005] In order to improve the cycle performance of these metal materials, a commonly used method is to alloy electrochemically active metals with electrochemically inert metals. For example, researchers have alloyed Sn with elements such as Cu, Sb, Ag, and Ni, which has improved the cycle performance to a certain extent, but the results are not ideal. In the reported research, mechanical alloying, chemical precipitation, solid-phase sintering of composite oxides, and sputtering coating have also been used. The above preparation methods are all aimed at obtaining fine tin particles dispersed and embedded in the inert components to improve the cycle capacity. However, the cycle performance of this type of material still needs to be further improved. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a dealloyed sodium ion battery negative electrode material and a preparation method thereof.

[0007] According to one aspect of the present invention, a dealloyed sodium ion battery negative electrode material is proposed, which is composed of solid carbon particles and nanoscale metal meshes coated on the surface of the solid carbon particles, or composed of nanoscale metal meshes and a carbon skeleton supported internally by the nanoscale metal meshes, wherein the carbon skeleton is hollow or three-dimensionally porous, and the nanoscale metal mesh is composed of at least one of Sn, Pb, Bi, Ge or Sb.

[0008] In some embodiments of the present invention, the particle size of the dealloyed sodium ion battery negative electrode material is 1-5 μm.

[0009] The present invention also provides a method for preparing the dealloyed sodium ion battery negative electrode material, comprising the following steps:

[0010] S1: adding carbon-containing particles to a mixed solution of hydrochloric acid and stannous chloride and boiling for a period of time, washing and then adding them to a mixed solution of hydrochloric acid and palladium chloride and boiling for a period of time, washing and then adding them to a sodium hypophosphite solution for immersion, solid-liquid separation, and obtaining carbon-containing particles with a metal palladium layer on the surface; the carbon-containing particles are hard carbon or organic polymers;

[0011] S2: adding the carbon-containing particles with a metal palladium layer on the surface into an electroplating solution, and plating the particles under stirring to obtain carbon-containing particles with an alloy coating; the electroplating solution contains Ni and at least one of Sn, Pb, Bi, Ge or Sb; plating under stirring can prevent particle agglomeration.

[0012] S3: introducing carbon monoxide into the carbon-containing particles with the alloy coating, and then adding them to a first organic solvent for immersion to obtain dealloyed particles; when the carbon-containing particles are organic polymers, proceed to step S4; when the carbon-containing particles are hard carbon, the dealloyed particles obtained in this step are finished products;

[0013] S4: Select any of the following methods: (1) carbonizing the dealloyed particles under an inert atmosphere to obtain; (2) soaking the dealloyed particles in a second organic solvent, then placing them in a carbon source solution for hydrothermal reaction, and then carbonizing them under an inert atmosphere to obtain; wherein the carbon-containing particles used in method (2) are soluble linear organic polymers. The purpose of soaking the dealloyed particles with a second organic solvent is to remove the carbon-containing particles inside. The particles obtained after carbonization in method (1) have a three-dimensional porous carbon skeleton inside, and the particles obtained after carbonization in method (2) have a hollow carbon skeleton inside. Both carbon skeletons play the role of supporting the nano-scale metal network.

[0014] In some embodiments of the present invention, in step S1, the carbon-containing particles are pre-treated as follows: the carbon-containing particles are added to a sodium hydroxide solution and heated, washed with water, then added to a nitric acid solution and heated, and then washed with water. The purpose of adding the sodium hydroxide solution is to remove surface dirt. Preferably, the concentration of the sodium hydroxide solution is 5-30%, heated to boiling, and boiled for 15-30 minutes; the purpose of the treatment with the nitric acid solution is to corrode the surface of the carbon-containing particles and enhance their bonding ability with the coating. Preferably, the concentration of the nitric acid solution is 15-25%, heated to boiling, and boiled for 15-25 minutes.

[0015] In some preferred embodiments of the present invention, in step S1, the solid-to-liquid ratios of the sodium hydroxide solution and the nitric acid solution during the treatment process are both 20-30 g / L.

[0016] In some embodiments of the present invention, in step S1, the particle size of the carbon-containing particles is ≤5 μm.

[0017] In some embodiments of the present invention, in step S1, the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and stannous chloride is 1.5-2.0 mol / L, and the concentration of stannous chloride is 15-20 g / L. The purpose of treating with the mixed solution of hydrochloric acid and stannous chloride is to adsorb a layer of easily oxidizable stannous ions on the surface of the carbon-containing particles. Preferably, the mixed solution of hydrochloric acid and stannous chloride is boiled for 10-20 min.

[0018] In some embodiments of the present invention, in step S1, the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and palladium chloride is 1.5-2.0 mol / L, and the concentration of palladium chloride is 0.5-1 g / L. The purpose of treating with the mixed solution of hydrochloric acid and palladium chloride is to reduce palladium ions to active metal palladium attached to the surface of carbon-containing particles. Preferably, the boiling time of the mixed solution of hydrochloric acid and palladium chloride is 10-20 min.

[0019] In some embodiments of the present invention, in step S1, the concentration of the sodium hypophosphite solution is 30-50 g / L, and the soaking time of the sodium hypophosphite solution is 10-20 min. The purpose of soaking with the sodium hypophosphite solution is to remove tin and palladium ions on the surface of the carbonaceous particles.

[0020] In some embodiments of the present invention, in step S1, the solid-to-liquid ratio of the mixed solution of hydrochloric acid and stannous chloride, the mixed solution of hydrochloric acid and palladium chloride, and the sodium hypophosphite solution during the treatment process is 40-60 g / L.

[0021] In some embodiments of the present invention, in step S1, the organic polymer is at least one of polystyrene, polyacetylene, polyaniline, polypyrrole or polythiophene.

[0022] In some embodiments of the present invention, in step S2, after the plating is completed, solid-liquid separation is performed, and the obtained solid is first washed with deionized water and then washed with anhydrous ethanol.

[0023] In some embodiments of the present invention, in step S2, the plating time is 5-10 minutes.

[0024] In some embodiments of the present invention, in step S3, the first organic solvent is at least one of benzene, acetone, ether, tetrachloronaphthalene, ethanol, chloroform or carbon tetrachloride.

[0025] In some embodiments of the present invention, in step S3, the pressure of carbon monoxide is ≥ 0.1 MPa, the treatment temperature is 38-93° C., and the treatment time is 0.5-1.0 h.

[0026] In some embodiments of the present invention, in step S4, the second organic solvent is a good solvent, preferably at least one of tetrahydrofuran, dichloromethane or chloroform.

[0027] In some embodiments of the present invention, in step S4, the carbon source solution is at least one of a solution of glucose, starch, sucrose, fructose, lactose or galactose; and the concentration of the carbon source solution is 0.05-2 g / mL.

[0028] In some embodiments of the present invention, in step S4, the solid-liquid ratio of the hydrothermal reaction is 1 g:(1-10) mL; the temperature of the hydrothermal reaction is 150-200° C., and the reaction time is 2-5 h.

[0029] In some embodiments of the present invention, in step S4, the carbonization temperature is 200-550° C., and the carbonization time is 1-12 h.

[0030] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:

[0031] 1. The present invention firstly performs a pre-plating treatment on the carbon-containing particles to obtain a metal palladium layer with catalytic activity on the surface, which is easy for the metal particles to adhere during the subsequent electroplating. Then, a nickel-containing electroplating solution is used for alloy electroplating, so that the target metal (Sn, Pb, Bi, Ge or Sb) and nickel are co-deposited on the surface of the carbon-containing particles. After a dealloying treatment, the nickel reacts with carbon monoxide to generate carbonyl nickel, which is dissolved by an organic solvent to remove the nickel, thereby forming a nano-scale metal mesh on the surface of the carbon-containing particles. When used as a negative electrode material, the nano-porous structure inside the carbon-containing particles can buffer the volume change caused by the charge and discharge process and increase the contact area between the electrode and the electrolyte, and has high capacity, excellent cycle and rate performance. At the same time, the metal produced by electroplating has a high density and mechanical strength. When used as a negative electrode material for charge and discharge, it can well resist the problems caused by its volume expansion.

[0032] 2. Since the electroplated metals have different melting points, they can be selectively carbonized. When the carbon-containing particles are selected as organic polymers, they can be carbonized to form a supporting three-dimensional porous carbon skeleton structure inside the particles. The carbon-containing particles can also be selected as linear organic polymers. After the metal mesh is prepared, the linear organic polymer inside the particles is removed with an organic solvent, and then the particles are soaked in a carbon source solution and carbonized to form a supporting hollow carbon skeleton structure inside the metal mesh. The combination of metal mesh and carbon material can improve the strength and conductivity of the particles, and the three-dimensional porous or hollow carbon skeleton structure can further increase the specific surface area of ​​the material, which is more conducive to the deintercalation of sodium ions. When used as a negative electrode material for sodium ion batteries, it can further improve the cycle performance and specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0034] Figure 1 This is a SEM image of the dealloyed sodium ion battery negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment prepares a dealloyed sodium ion battery negative electrode material, which consists of solid carbon particles and nano-scale metal mesh coated on the surface of the solid carbon particles, with a particle size of 1-5 μm. The preparation process is as follows:

[0038] (1) Pre-plating treatment: Select hard carbon with a particle size of ≤5 μm, add it to a 20% sodium hydroxide solution, boil it for 20 minutes (to remove surface dirt), wash it with deionized water until it is neutral, then add it to a 20% nitric acid solution, boil it for 20 minutes (to corrode the particle surface and enhance its bonding ability with the coating), wash it with deionized water until it is neutral, and the solid-liquid ratio of the treatment process is 25 g / L;

[0039] (2) adding the hard carbon treated in step (1) to a 1.5 mol / L HCl and 20 g / L stannous chloride solution and boiling for 15 min (adsorbing a layer of easily oxidizable stannous ions), washing with deionized water until neutral, then adding to a 1.5 mol / L HCl and 0.5 g / L palladium chloride solution and boiling for 20 min (reducing the palladium ions to active metal palladium attached to the particle surface), washing with deionized water until neutral, then adding to a 50 g / L sodium hypophosphite solution and soaking for 20 min (removing tin and palladium ions on the particle surface), solid-liquid separation and drying, the solid-liquid ratio of the treatment process is 50 g / L;

[0040] (3) Preparation of nickel alloy plating solution: The composition of the alloy plating solution is 50 g / L SnCl2, 280 g / L NiCl2, 50 g / L (NH4)HF2, pH is 2-2.5, and the current density is 1-2 A / dm 2 , the temperature is 60℃;

[0041] (4) electroplating: adding the hard carbon treated in step (2) into the alloy electroplating solution, and electroplating for 8 minutes under stirring;

[0042] (5) Dealloying treatment: After electroplating, the solid and liquid are separated. The solid is first washed with deionized water and then with anhydrous ethanol. Carbon monoxide is introduced into the obtained particles for treatment for 0.5 h. The pressure of carbon monoxide is ≥0.1 MPa and the treatment temperature is 60°C. Acetone is added for immersion. After solid-liquid separation, dealloyed sodium ion battery negative electrode material is obtained.

[0043] Example 2

[0044] This embodiment prepares a dealloyed sodium ion battery negative electrode material, whose structure consists of a nano-scale metal mesh and a three-dimensional porous carbon skeleton supported internally, with a particle size of 1-5 μm. The preparation process is as follows:

[0045] (1) Pre-plating treatment: Select polystyrene with a particle size of ≤5 μm, add it to a 15% sodium hydroxide solution, boil it for 15 minutes (to remove surface dirt), wash it with deionized water until it is neutral, then add it to a 15% nitric acid solution, boil it for 15 minutes (to corrode the particle surface and enhance its bonding ability with the coating), wash it with deionized water until it is neutral, and the solid-liquid ratio of the treatment process is 20 g / L;

[0046] (2) adding the polystyrene treated in step (1) to a 2.0 mol / L HCl and 15 g / L stannous chloride solution and boiling for 20 min (adsorbing a layer of easily oxidizable stannous ions), washing with deionized water until neutral, then adding to a 1.5 mol / L HCl and 1 g / L palladium chloride solution and boiling for 20 min (reducing the palladium ions to active metal palladium attached to the particle surface), washing with deionized water until neutral, then adding to a 30 g / L sodium hypophosphite solution and soaking for 10 min (removing tin and palladium ions on the particle surface), and drying after solid-liquid separation. The solid-liquid ratio of the treatment process is 40 g / L;

[0047] (3) Preparation of nickel alloy plating solution: The composition of the alloy plating solution is 45g / L SnCl2, 285g / L NiCl2, 55g / L (NH4)HF2, pH is 2-2.5, and the current density is 1-2A / dm 2 , temperature is 70℃;

[0048] (4) electroplating: adding the polystyrene treated in step (2) into the alloy electroplating solution, and electroplating for 7 minutes under stirring;

[0049] (5) Dealloying treatment: After the electroplating is completed, the solid and liquid are separated, the solid is first washed with deionized water, and then washed with anhydrous ethanol, and carbon monoxide is introduced into the obtained particles for treatment for 1.0 h, the pressure of carbon monoxide is ≥0.1 MPa, the treatment temperature is 70°C, and ethanol is added for immersion. After solid-liquid separation, dealloyed sodium particles are obtained;

[0050] (6) Carbonization treatment: The dealloyed sodium particles obtained in step (5) are carbonized, wherein the carbonization is carried out under an inert atmosphere at 215° C. for 12 h to obtain a dealloyed sodium ion battery negative electrode material.

[0051] Example 3

[0052] This embodiment prepares a dealloyed sodium ion battery negative electrode material, whose structure consists of a nano-scale metal mesh and a hollow carbon skeleton supported internally, with a particle size of 1-5 μm. The preparation process is as follows:

[0053] (1) Pre-plating treatment: Select polystyrene with a particle size of ≤5 μm, add it to a 30% sodium hydroxide solution, boil it for 30 minutes (to remove surface dirt), wash it with deionized water until it is neutral, then add it to a 25% nitric acid solution, boil it for 25 minutes (to corrode the particle surface and enhance its bonding ability with the coating), wash it with deionized water until it is neutral, and the solid-liquid ratio of the treatment process is 30 g / L;

[0054] (2) adding the polystyrene treated in step (1) to a 2.0 mol / L HCl and 20 g / L stannous chloride solution and boiling for 20 min (adsorbing a layer of easily oxidizable stannous ions), washing with deionized water until neutral, then adding to a 2.0 mol / L HCl and 1 g / L palladium chloride solution and boiling for 20 min (reducing the palladium ions to active metal palladium attached to the particle surface), washing with deionized water until neutral, then adding to a 50 g / L sodium hypophosphite solution and soaking for 20 min (removing tin and palladium ions on the particle surface), solid-liquid separation and drying, the solid-liquid ratio of the treatment process is 60 g / L;

[0055] (3) Preparation of nickel alloy plating solution: The composition of the alloy plating solution is 30 g / L PbCl2, 45 g / L NiCl2, 50 g / L NH2SO3H, 120 g / L HEDP, 10 g / L hydrazine hydrochloride, pH 9-10, current density 0.5-1 A / dm 2 , temperature is 25℃;

[0056] (4) Electroplating: Add the S2 treated carbonaceous particles into the electroplating solution and perform electroplating under stirring for 8 minutes;

[0057] (5) Dealloying treatment: After the electroplating is completed, the solid and liquid are separated, and the solid is first washed with deionized water and then with anhydrous ethanol. Carbon monoxide is introduced into the obtained particles for treatment for 0.7 h. The pressure of carbon monoxide is ≥0.1 MPa and the treatment temperature is 80°C. Ether is added for immersion. After solid-liquid separation, dealloyed particles are obtained;

[0058] (6) Carbonization treatment: The dealloyed particles were immersed in dichloromethane to remove the polystyrene inside, and then added to a 1 g / mL starch solution for a hydrothermal reaction. The solid-liquid ratio of the hydrothermal reaction was 1 g:2 mL, the reaction temperature was 160 °C, and the reaction time was 3 h. After the reaction was completed, the solid was collected and carbonized. The carbonization process was carried out at 215 °C in an inert atmosphere for 12 h to obtain the dealloyed sodium ion battery negative electrode material.

[0059] Comparative Example

[0060] In this comparative example, a Sn / C composite material was prepared by carbothermal reduction method, and the specific process was as follows:

[0061] SnO2 and activated carbon powder with a molar ratio of 1:3 were ground in an agate mortar and mixed evenly. The mixture was loaded into a porcelain boat and placed in a tube furnace. Under argon protection, the temperature was raised to 950°C at 5°C / min, kept for 8 hours, and then naturally cooled to room temperature to obtain a Sn / C composite material. The material is mainly composed of Sn spherical particles and block-shaped activated carbon. The Sn spheres are evenly dispersed and adsorbed on the block-shaped activated carbon. The size of the Sn spherical particles is about 0.5-7μm.

[0062] Test example

[0063] The sodium ion battery negative electrode materials prepared in Examples 1-3 and the comparative example were used to prepare lithium ion battery negative electrode sheets, and button batteries were assembled and tested at a current density of 200 mA / g and a voltage range of 0.001-2.0 V. The results are shown in Table 1.

[0064] Table 1

[0065]

[0066] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A dealloyed sodium ion battery negative electrode material, characterized in that: It is composed of solid carbon particles and a nano-scale metal mesh coated on the surface of the solid carbon particles, or it is composed of a nano-scale metal mesh and a carbon skeleton supported by the nano-scale metal mesh, wherein the carbon skeleton is hollow or three-dimensionally porous, and the composition of the nano-scale metal mesh is one of Sn, Pb, Bi, Ge or Sb; The dealloyed sodium ion battery negative electrode material is obtained by the following method: firstly, carbon-containing particles are subjected to pre-plating treatment to obtain a metal palladium layer with catalytic activity on the surface, and then an electroplating solution containing nickel and a target metal is used for alloy electroplating to make the target metal and nickel co-deposit on the surface of the carbon-containing particles, and after dealloying treatment, nickel and carbon monoxide react to generate carbonyl nickel, and nickel is removed by dissolving with an organic solvent, thereby forming a nano-scale metal network on the surface of the carbon-containing particles, and the target metal is one of Sn, Pb, Bi, Ge or Sb.

2. The dealloyed sodium ion battery negative electrode material according to claim 1, characterized in that: The particle size of the dealloyed sodium ion battery negative electrode material is 1-5 μm.

3. The method for preparing a dealloyed sodium ion battery negative electrode material according to claim 1, characterized in that: The following steps are involved: S1: adding carbon-containing particles to a mixed solution of hydrochloric acid and stannous chloride and boiling for a period of time, washing and then adding them to a mixed solution of hydrochloric acid and palladium chloride and boiling for a period of time, washing and then adding them to a sodium hypophosphite solution for immersion, solid-liquid separation, and obtaining carbon-containing particles with a metal palladium layer on the surface; the carbon-containing particles are hard carbon or organic polymers; S2: adding the carbon-containing particles with a metal palladium layer on the surface into an electroplating solution, and plating under stirring to obtain carbon-containing particles with an alloy coating; the electroplating solution contains Ni and one of Sn, Pb, Bi, Ge or Sb; S3: introducing carbon monoxide into the carbon-containing particles with the alloy coating, and then soaking them in a first organic solvent to obtain dealloyed particles; when the carbon-containing particles are organic polymers, proceeding to step S4; S4: any one of the following methods is selected: (1) carbonizing the dealloyed particles under an inert atmosphere to obtain; (2) soaking the dealloyed particles in a second organic solvent until the carbon-containing particles inside are removed, then placing them in a carbon source solution for hydrothermal reaction, and then carbonizing them under an inert atmosphere to obtain; wherein the carbon-containing particles used in method (2) are soluble linear organic polymers.

4. The preparation method according to claim 3, characterized in that: In step S1, the carbon-containing particles are pre-treated as follows: the carbon-containing particles are added to a sodium hydroxide solution and heated, washed with water, then added to a nitric acid solution and heated, and then washed with water.

5. The preparation method according to claim 3, characterized in that: In step S1, the particle size of the carbon-containing particles is ≤5 μm.

6. The preparation method according to claim 3, characterized in that: In step S1, the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and stannous chloride is 1.5-2.0 mol / L, and the concentration of stannous chloride is 15-20 g / L.

7. The preparation method according to claim 3, characterized in that: In step S1, the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and palladium chloride is 1.5-2.0 mol / L, and the concentration of palladium chloride is 0.5-1 g / L.

8. The preparation method according to claim 3, characterized in that: In step S1, the organic polymer is at least one of polystyrene, polyacetylene, polyaniline, polypyrrole or polythiophene.

9. The preparation method according to claim 3, characterized in that: In step S3, the first organic solvent is at least one of benzene, acetone, ether, tetrachloronaphthalene, ethanol, chloroform or carbon tetrachloride.

10. The preparation method according to claim 3, characterized in that: In step S4, the carbon source solution is at least one of a solution of glucose, starch, sucrose, fructose, lactose or galactose.

Citation Information

Patent Citations

  • Lithium ion battery negative electrode composite material and preparation method thereof

    CN106848219A

  • Lithium ion power battery composite negative electrode material and preparation method thereof

    CN111933941A